Risk Factors for Mortality Among Older Adults with Hospital-Acquired Bloodstream Infections in the Intensive Care Unit: A Multicenter Cohort Study - Tomer Hoffman; Ili Margalit; Alexis Tabah; Stéphane Ruckly; François Barbier; Pierre Singer; Jean-François Timsit; Virginie Prendki; Nasreen Hassoun-Kheir; Niccolò Buetti; Dafna Yahav; the EUROBACT-2 Study Group, the European Society of Intensive Care Medicine (ESICM), the European Society of Clinical Microbiology, Infectious Diseases (ESCMID) Study Groups for Infections in Critically Ill Patients (ESGCIP), Infections in the Elderly (ESGIE), the OUTCOMEREA Network (Infectious Diseases and Therapy)
Abstract Introduction We aimed to investigate risk factors for mortality among older adults (≥ 75 years) with hospital-acquired bloodstream infections (HA-BSI) in the intensive care unit (ICU). Methods We included patients aged ≥ 75 years with HA-BSI in ICU from the EUROBACT-2 cohort (2019–2021). Univariable and multivariable analyses were conducted to identify predictors of 28-day mortality. Results The cohort included 563 patients (median age 80, 39% women). Mortality at 28 day was 50%. Factors associated with mortality in multivariate analysis were admission due to COVID-19, failure to achieve source control, and higher SOFA. Among older adults with Gram-negative BSI, corticosteroid administration for septic shock was an additional factor. Among functionally independent patients, age itself was not associated with mortality. Conclusions HA-BSI in older adults in ICU are associated with high mortality. Inadequate source control is a significant modifiable risk factor. The use of corticosteroids in ICU management of older adults should be further investigated.